Internet censorship detected in Iran (Iran) - Voidly (Voidly Global Censorship Index, 2026)
WARNING severity censorship detected in Iran. Data sourced from CensoredPlanet.
Censorship Incident ID: IR-2026-0426. Severity: warning. Confidence: 65%